THU0229 Is There A Difference in The Presentation of Diffuse and Limited Subtype in Childhood? Results from The Juvenile Scleroderma Inception Cohort. (15th July 2016) - Foeldvari, I.; Klotsche, J.; Kasapcopur, O.; Adrovic, A.; Terreri, M.T.; Stanevicha, V.; Katsikas, M.M.; Alexeeva, E.; Sztajnbok, F.; Cimaz, R.; Kostik, M.; Sifuentes-Giraldo, W.A.; et al.
Abstract : Background: Juvenile systemic sclerosis (jSSc) is an orphan autoimmune disease. Several adult publications looked at the differences between limited (ljSSc) and diffuse subtype (djSSc). There is rarity of data regarding this topic in pediatric jSSc. The juvenile scleroderma inception cohort is a prospective standardized register for patients with jSSc. Objectives: comparison of patients characteristic at the time of inclusion with ljSSc and djSSc Methods: We compered the demographics and clinical characteristics of the ljSSc and djSSc. Results: Up till now 74 patients were enrolled, 54 (76%) with djSSc and 18 with ljSSc (24%). 9% in djSSc and 25% in ljSSc showed overlap features. Disease duration at time of inclusion in the cohort was 3.7 years in the djSSc and 3.3 years in ljSSc. 82% in the djSSc and 78% in the ljSSc group were female. The mean age of the onset of Raynaud symptomatic was 9.0 years in the jdSSc and 9.9 years in ljSSc group and onset of the non-Raynaud symptomatic with 9.4 in djSSc and 10.6 ljSSc. At the time of inclusion the mean modified Rodnan Skin Score was 18.5 in the djSSc and 8, 4 in ljSSc (p=0.0001). Anti-Scl 70 positivity was found in 31.5% of djSSc and 30.8% in ljSSc. Only 2 patient in the djSSc group and one in the ljSSc group was anticentromere positive. Capillary changes occurred in 60.7% in the djSSc and 50% in ljSSc, but 58.2% in djSSc and only 23.5% in ljSSc had already history of ulcerations (p=0.013) and 21.8% had active ulceration in the djSSc and 5.9% in the ljSSc. 33.3% of djSSc and 72.7% of ljSSc had cardiac involvement (p=0.027). pulmonary hypertension occurred in 57.1% djSSc and 18.2% in ljSSc. 63% in djSSc and 27.3% in ljSSc group had signs of interstitial lung disease on imaging (p=0.046). Renal involvement occurred in 7.1% djSSc and 5.6% in ljSSc. 39.3% of djSSc and 22.2% of ljSSc had gastrointestinal involvement. 56.4% in djSSc and 83.35 in ljSSc had musculoskeletal involvement (p=0.04). Conclusions: Patients with djSSc have younger age at onset, have more often capillary changes and active ulcerations, pulmonary hypertension and less gastorintestinal and joint involvement and more disease damage. The characteristics of the pediatric subtypes differs from adults with SSc, especially the high proportion of patients with diffuse subtype. Disclosure of Interest: None declared